Relationship of Doctor Ratio with Non-Specialistic Referrals Status in Social Security Agency on Health, Pamekasan - Trisno, Zetiawan; Raihan, Wardatul; Zahroh, Qorinatus (Universitas Teuku Umar, 2024)
Increased access to health services after universal health coverage has not been matched by the fulfillment of the ratio of doctors will disrupt the resilience of national health insurance. The role of doctors in first-level health facilities as health service providers and referral screeners (gate keepers). This gap in the ratio of doctors can lead to high rates of non-specialistic referrals. This study aims to analyze the relationship between the ratio of doctors to Non-Specialistic Referrals (RNS) at BPJS Kesehatan Pamekasan Branch Office. The research method used was quantitative with an observational analytic approach using cross sectional and secondary data derived from all Status in Social Security Agency on Health, Pamekasan and Sumenep districts, and analyzed with the chi-square test (α=0.05). The results of this study indicate the existence of a doctor's ratio on the status of non-specialistic referrals, namely there is a relationship with a p-value of 0.001<0.05; OR=2.381 CI= 1.099-3.574. The conclusion of this study shows that there is a relationship between the ratio of doctors to the status of non-specialistic referrals. Local governments are expected to develop strategies to fulfill the ratio of doctors, especially in first-level facilities to achieve quality and standardized health services